Pengembangan Pariwisata Berbasis Masyarakat Untuk Mendukung Wisata Agro di Dusun Mekarmulya Pangandaran - Mezi Julian (Lembaga Pengembangan Kinerja Dosen, 2025)
This research studies the model of community based tourism development activities in supporting the agri-tourism in Dusun Mekarmulya, Desa Bangunkarya, Kecamatan Langkaplancar, Kabupaten Pangandaran. The process of community based tourism consisted of eight stages; Embryonic stage, Germination stage, Involvement, Consolidated involvment, Development, Consolidation, Stagnation, and Decline. Penentuan posisi daam CBT ini berdasarkan pada 4 key elements of CBT yaitu; Natural and Cultural Resources, Community Organization, Management, and Learning. Method of data collection is conducted through interviews, field observations, and documentation study. Then, the collected data is used to perform triangulation process. This research had led to the finding that Dusun Mekarmulya is now in the Germination stage. The result of this research is that development of community-based tourism in Mekarmulya should step into the next stage of the CBT’s stage to develop the tourism.